Cultural practices affecting the rate of fusarium damage in durum wheats - Pérez-Marco P. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Under water stress conditions, 'white head' appearance caused by Fusarium in durum wheat, was associated with nitrogen fertilization. In a dry season, all the agronomic practices leading to drought increase, such a high plant density or spring nitrogen fertilisation, produce an increase on the number of plants affected. Although all the tested entries were susceptible, differences in performance among then were detected.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)